Frontal lobe neurology and the creative mind - de Souza, Leonardo C.; Guimarães, Henrique C.; Teixeira, Antônio L.; Caramelli, Paulo; Levy, Richard; Dubois, Bruno; Volle, Emmanuelle (Frontiers in Psychology, 2014)
Concepts from cognitive neuroscience strongly suggest that the prefrontal cortex (PFC) plays a crucial role in the cognitive functions necessary for creative thinking. Functional imaging studies have repeatedly demonstrated the involvement of PFC in creativity tasks. Patient studies have demonstrated that frontal damage due to focal lesions or neurodegenerative diseases are associated with impairments in various creativity tasks. However, against all odds, a series of clinical observations has reported the facilitation of artistic production in patients with neurodegenerative diseases affecting PFC, such as frontotemporal dementia (FTD). An exacerbation of creativity in frontal diseases would challenge neuroimaging findings in controls and patients, as well as the theoretical role of prefrontal functions in creativity processes. To explore this paradox, we reported the history of a FTD patient who exhibited the emergence of visual artistic productions during the course of the disease. The patient produced a large amount of drawings, which have been evaluated by a group of professional artists who were blind to the diagnosis. We also reviewed the published clinical cases reporting a change in the artistic abilities in patients with neurological diseases. We attempted to reconcile these clinical observations to previous experimental findings by addressing several questions raised by our review. For instance, to what extent can the cognitive, conative and affective changes following frontal damage explain changes in artistic abilities? Does artistic exacerbation truly reflect increased creative capacities? These considerations could help to clarify the place of creativity - as it has been defined and explored by cognitive neuroscience - in artistic creation and may provide leads for future lesion studies.